Generation Z’s Engagement in Palestine Advocacy on TikTok - Maulida Muflihah, Istikana; Danang Purwanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The public sphere serves as a platform where individuals can openly and fairly share ideas and knowledge without the influence of particular authorities, fostering democratic discussions. Today, social media holds the potential to create a public sphere for its users, functioning not only as a channel for information exchange but also as a platform for social advocacy on global issues. TikTok, a popular social media among Generation Z, provides a space for their engagement in global issues, including the Palestinian solidarity movement. The involvement of Generation Z in TikTok allows them to access and voice their perspectives on global matters, making this platform a public sphere that supports social participation and advocacy on an international level. This study employs qualitative phenomenology with Jürgen Habermas’ public sphere theory to analyze how TikTok forms a public sphere. The study aims to understand why Generation Z uses TikTok as a medium for social advocacy, specifically in supporting Palestinian solidarity. Findings indicate that TikTok functions as a public sphere aligned with Habermas' theory, effectively providing Generation Z with a space for expressing support for Palestine. TikTok's characteristics enable open interaction and participation, meeting Generation Z’s need for engagement in global issues and active social advocacy.